Childhoods and play: Facebook, exhibition and competition - Duek Carolina (French Journal for Media Research, 2014)
L'objectif de ce document vise à explorer les relations entre le jeu et les enfants dans le contexte contemporain. L'article considère le jeu d'enfants comme pratique significative à partir des nouvelles technologies de l'information et de la communication.  Comme les enfants associent  Facebook aux jeux, Facebook représente le point central de cet article. Nous traitons les jeux auxquels les enfants jouent, les articulations les plus appropriées entre les enfants, la socialisation et Facebook. Nous proposons d'entrer dans l'univers où les enfants, les représentations, les médias et les adultes entrent en relation. Nous analysons Facebook comme la plate-forme contemporaine la plus importante à partir de laquelle la socialisation, l'exposition et la concurrence sont construites par les enfants.The objective of this paper is to explore the relationship between games, play and children in the contemporary context. The article begins with the consideration of children’s play as a meaningful practice focussing on new technologies of information and communication. Along the research, Facebook was identified as the most important place that children associated with games. That is why, the role that Facebook “plays” is one of the most important focusses of this paper: the uses that our informants report of the most used social network, the games they play and the most relevant articulations between children, socialization and Facebook. It is not our objective to analyse games thoroughly (we will analyse “Farmville” briefly), but to enter the universe in which children, representations, media and adults are related and intertwined. And in this path, we will analyse Facebook as the most important contemporary platform from which socialization, exhibition and competition are built by children as the main subjects of our research.